Improved adsorption properties of tetracycline on KOH/KMnO4 modified biochar derived from wheat straw. (June 2022) - Xu, Jin; Zhang, Yin; Li, Bin; Fan, Shisuo; Xu, Huacheng; Guan, Dong-Xing
Abstract: Modification of pristine biochars has received increasing attentions due to the significant potential in enhancing adsorption performance. In this work, the co-modification of KOH and KMnO4 on biochar (K-Mn-BC) was performed, with the effect of KOH/KMnO4 modification on biochar properties and their adsorption toward tetracycline (TC) being extensively explored. Results showed that KOH/KMnO4 modification can significantly regulate biochars to form hierarchical structure. The obtained K-Mn-BC was characterized with a high specific surface area (1524.6 m 2 g −1 ) and total pore volume (0.85 cm 3 g −1 ). In addition, the K-Mn-BC exhibited a high adsorption capacity of 584.19 mg g −1 toward TC at 318 K, and pseudo-second-order ( R 2 :0.993～0.998) and Langmuir ( R 2 : 0.834～0.874) models can fit well with the adsorption behavior. Moreover, the obtained K-Mn-BC can efficiently adsorb TC within a wide pH range (3.0–10.0), and were not affected by the co-existing ions. The possible mechanisms for the high adsorption capacity were ascribed to the pore filling and π-π interaction, following by hydrogen bonding and metal complexation. The obtained K-Mn-BC is a suitable adsorbent for TC removal from water due to the hierarchical structure, high adsorption capacity, and stable adsorption effect. Graphical abstract: Image 1 Highlights: Co-modification of KOH and KMnO4 on biochar for enhanced TC adsorption was studied. K-Mn-BC exhibited a hierarchical structure. Pseudo-second-order and Langmuir models can well fit the adsorption behavior. The maximum adsorption capacity of K-Mn-BC toward was 584.19 mg g −1 . The prevailing mechanisms of TC on K-Mn-BC were revealed.